Spinacetin Suppresses the Mast Cell Activation and Passive Cutaneous Anaphylaxis in Mouse Model - Ji, Ning; Pan, Shunli; Shao, Chen; Chen, Yufen; Zhang, Zhe; Wang, Ran; Qiu, Yuling; Jin, Meihua; Kong, Dexin (Frontiers in Pharmacology, 2018)
We previously reported the anti-inflammatory and anti-asthmatic activities of the extract of the Inula japonica Thunb. Aiming for discovery of a novel anti-inflammatory compound, we isolated spinacetin from the extract and investigated its in vitro and in vivo anti-inflammatory effect and the related mechanism. Effect of spinacetin on the Syk signaling pathway was studied in bone marrow-derived mast cells (BMMCs), and that on the nuclear factor-κB (NF-κB) and mitogen-activated protein kinases (MAPKs) was investigated in Rat basophilic leukemia (RBL)-2H3 cells and human mast cell line (HMC-1). The in vivo anti-inflammatory activity was assessed with passive cutaneous anaphylaxis (PCA) reaction assay. Spinacetin significantly inhibited the release of histamine, and production of inflammatory mediators such as leukotriene C4 (LTC4) and interlukin-6 (IL-6) in IgE/Ag stimulated BMMCs. Analysis of the signaling pathways demonstrated that spinacetin inhibited activation of Syk, linker of activated T cells (LAT), phospholipase Cγ(PLCγ), cytosolic phospholipase A2 (cPLA2), MAPKs, Akt/ NF-κB, and intracellular Ca2+ mobilization but with no effect on Fyn and Lyn. On the other hand, spinacetin suppressed IgE/Ag-induced activation of RBL-2H3 cells with inhibition against phosphorylation of extracellular signal regulated-protein kinase (ERK), c-Jun-NH2-terminal kinase (JNK), p38 MAPKs, PLCγ, translocation of cPLA2, and Akt/IκBα/NF-κB signal. However, spinacetin had no effect on PMA and A23187-induced activation of HMC-1. Furthermore, oral administration of spinacetin dose-dependently attenuated IgE/Ag-mediated PCA reaction in mouse model. Taken together, spinacetin showed the activities in preventing inflammatory processes, which might be at least partially attributed to the abolishment of Syk-dependent activation of IgE/Ag-mediated mast cells.